High precision test of the Pauli Exclusion Principle for electrons. (August 2020) - Piscicchia, K; Amirkhani, A; Bartalucci, S; Bertolucci, S; Bazzi, M; Bragadireanu, M; Cargnelli, M; Clozza, A; Curceanu, C; Del Grande, R; De Paolis, L; Egger, J; et al.
Abstract: The VIP collaboration is performing high precision tests of the Pauli Exclusion Principle for electrons in the extremely low cosmic background environment of the Underground Gran Sasso Laboratories of INFN (Italy). The experimental technique consists in introducing a DC current in a copper conductor, searching for the X-rays emission due to a PEP-forbidden atomic transition from the L shell to the K shell of copper when the K shell is already occupied by two electrons. VIP set un upper limit on the PEP violation probability 1 2 β 2 < 4.7 × 10 − 29, the aim of the upgraded VIP-2 experiment is to improve this result by two orders of magnitude at least. The experimental setup and the results of preliminary data analyses will be presented.